Hello! The function f(x) = -x + 2 can be formed by shifting the function y = -2/3x vertically up by 2 units.
To see this, let's compare the two functions:
f(x) = -x + 2
y = -2/3x
If we set y = f(x), we get:
y = -x + 2
To transform y = -2/3x into this form, we need to shift the graph of y = -2/3x up by 2 units. This is equivalent to adding 2 to the y-value of each point on the graph.
Therefore, the correct answer is A: vertical shift up 2.
Please give me brainliest for more high quality answers! - longstretch